2016
DOI: 10.1109/jqe.2016.2587099
|View full text |Cite
|
Sign up to set email alerts
|

Concealment of Chaos Time-Delay Signature in Three-Cascaded Vertical-Cavity Surface-Emitting Lasers

Abstract: The time-delay signature and chaos bandwidth in three-cascaded vertical-cavity surface-emitting lasers (VCSELs) has been investigated experimentally. A peak value of autocorrelation coefficient at the feedback round trip time and the ratio between this peak value and its background are used to quantitatively identify the time-delay (TD) signature of chaos. A new conceptpeak to side-peak ratio is introduced for better quantification of the TD signature concealment. The peak to side-peak ratio is defined as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…Outside the injection locking region, it is possible to cancel TDS and enhance bandwidth in SSRL at the same time, as can be seen from both figures. However, such region for achieving both goals is narrow, which confirms previous observations in cascaded-coupled systems consisting of conventional EELs [35] or VCSELs [34].…”
Section: Figuresupporting
confidence: 88%
“…Outside the injection locking region, it is possible to cancel TDS and enhance bandwidth in SSRL at the same time, as can be seen from both figures. However, such region for achieving both goals is narrow, which confirms previous observations in cascaded-coupled systems consisting of conventional EELs [35] or VCSELs [34].…”
Section: Figuresupporting
confidence: 88%
“…This further confirms that the suppression of TD signatures and complexity enhancement are achieved, providing that the operation of the master-slave system stays away from injection locking. This has also been previously observed and explained for other optically injected laser systems [16,18]. Moreover, one can also notice the difference in complexity between the regions where all time-delays are effectively suppressed and where only the delay multiples can be identified [see Fig.…”
Section: M-srl Under Cross-feedbacksupporting
confidence: 80%
“…Particularly for chaos-based communications, early works on chaotic lasers with feedback showed that even when the TD signature is concealed in the intensity dynamics I(t) [8], it may in some cases still be inferred by applying the same identifiers to the optical phase dynamics ϕ(t) [9]. For these reasons, novel approaches for suppressing the TD signature in chaotic sources have been reported [10][11][12][13][14][15][16][17][18][19]. Optical injection has been shown as a possible way to generate enhanced chaotic signals, exhibiting suppressed TD signatures, improved chaos bandwidth and dynamical complexity.…”
Section: Introductionmentioning
confidence: 99%
“…VCSELs subject to suitable optical feedback can generate high Kaplan-Yorke dimension optical chaotic output and then apply to optical-chaos-based communication [1,2,7]. However, the chaotic output from external cavity feedback VCSELs (ECF-VCSELs) usually retains a time-delay signature (TDS) originated from the optical round trip between the VCSEL and the external feedback mirror [8][9][10][11][12][13][14], which may provide some possibilities to reconstruct the system by adopting time-series analysis techniques for delayed systems [15][16][17] and then threaten the system security. As a result, the TDS suppression has been a research hot spot in the field related to chaos generation and applications based on delayed VCSELs in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al proposed a three cascade-coupled configuration of VCSELs and numerically investigated the TDS and chaotic bandwidth of the output from the VCSELs [13]. Hong et al experimentally verified the performance of the threecascaded VCSELs in suppressing the TDS of chaos as well as the effect of injecting chaotic bandwidth on the TDS suppression [14]. It should be noted that, for the abovementioned schemes, external optical feedback is provided by mirrors.…”
Section: Introductionmentioning
confidence: 99%